(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to describe the comparison analysis of part, whole, and imagery learning method in basketball games. The whole section method is generally used by an educator to teach a form of movement skills that is quite difficult or complex. This method is very helpful for Physical Education Sports and Health (PJOK) teachers in carrying out teaching and learning processes specially to help students who have difficulty learning a series of movements that are just known and have a high degree of difficulty. To anticipate the complexity and diversity of the movements, it is necessary to make a kind of simplification in advance of the movements to be learned into parts so that they are easily understood and learned by students. This approach will be good (effective) if the parts per part of the movement studied are understood or mastered first then combined into a whole movement, but on the contrary it becomes ineffective if students directly learn the movement in a whole direction. The overall learning method is a form of learning skills that are carried out in full from the skills learned, this is the opposite of the parts-by-part method because in this learning method physical education educators from the beginning of the students have been directed to carry out the desired motion activities and generally the motion activities this is easy for students to do. This study used 37 students, the findings of the research conducted were that predicting the future using the method of imagination is highly dependent on student abilities and characteristics of motor skills.